OPTIMIZATION OF TAX RATES: AS A FACTOR FOR INCREASING INVESTMENT ATTRACTIVENESS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article provides a scientific and empirical analysis of the policy of optimizing tax rates[1] in the Republic of Uzbekistan for the period 2022–2024 and its impact on investment attractiveness. The relevance of studying the impact of tax policy on the investment climate is examined, in particular, the reduction of the value-added tax (VAT) rate from 15 percent to 12 percent starting in 2023, the retention of the profit tax rate at 15 percent[2], as well as important issues related to the dynamics of foreign direct investment (FDI). The results of the study show that reducing and simplifying tax rates is an effective tool for improving the business environment, expanding the tax base, and increasing investment attractiveness. The volume of FDI entering Uzbekistan in 2024 amounted to 2.836 billion US dollars, an increase of 31.5% compared to 2023.[3] The article presents practical proposals and recommendations for further optimization of tax rates. Comparative analysis, economic and statistical methods, and data from OECD, UNCTAD, and the World Bank were used as the research